2005
DOI: 10.1093/bjaceaccp/mki006
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections

Abstract: ВведениеБазовые принципы ведения неврологических и нейрохирургических пациентов при развитии у них критического состояния не отличаются от таковых у других реанимационных пациентов. Однако патогенез церебральных катастроф обладает рядом особенностей [1][2][3][4], которые иногда столь важны, что именно они определяют исход заболевания.Целесообразность создания специализированных отделений реанимации для пациентов неврологическо го и нейрохирургического профиля была доказана при проведении мета анализа, основанн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 3 publications
4
80
0
3
Order By: Relevance
“…ICU-HAI rates are higher than in general hospital wards due to the complex interactions between, the patient's underlying diseases, comorbidities, severity of illness, type of ICU, length of stay, and use of multiple invasive devices [2,18]. A study conducted in patients with hematological malignancies admitted to the ICU showed that mechanical ventilation and ≥2 organ failures were independently associated with in-hospital mortality.…”
Section: Page 10 Of 22mentioning
confidence: 99%
“…ICU-HAI rates are higher than in general hospital wards due to the complex interactions between, the patient's underlying diseases, comorbidities, severity of illness, type of ICU, length of stay, and use of multiple invasive devices [2,18]. A study conducted in patients with hematological malignancies admitted to the ICU showed that mechanical ventilation and ≥2 organ failures were independently associated with in-hospital mortality.…”
Section: Page 10 Of 22mentioning
confidence: 99%
“…21 Respiratory infections with S. aureus are common in patients with compromised airway defenses and hospitalized patients. 22 Previous studies also found P. aeruginosa and S. aureus to be the most frequent organism isolated from the culture of the tracheal swab. 7,10,23 In a study by Inweregbu K et al, S. aureus and P. aeruginosa were the most common pathogens associated with nosocomial pneumonia in intensive care unit.…”
Section: Discussionmentioning
confidence: 93%
“…Nosocomial infections (NI): "defined as those occurring within 48 hours of hospital admission, 3 days of discharge or 30 days of an operation" (1). NI are a Major complication in pediatric patients at different hospital wards.…”
Section: Introduction:-mentioning
confidence: 99%